PERAN CITRA MEREK DALAM MEMEDIASI PENGARUH POSITIONING TERHADAP KEPUTUSAN PEMBELIAN - Fathur Rosi; Nurita Andriani (Management Department of Economics and Business Of Trunojoyo Madura University, 2021)
This study discusses the problems that exist in one of the MSMEs in Bangkalan, namely KUB Bejrah Ghunah, the phenomenon in this company is good positioning but sales turnover according to the brand used has a bad perception in the minds of consumers. This study aims to determine the effect of positioning on purchasing decisions mediated by brand image. This study uses a quantitative approach with path analysis method, with a total of 100 respondents. The results showed that 1) positioning had a significant effect on purchasing decisions with tcount of 7.959 t table, namely 1.9847 with a significance level of 0.000 less than 0.05. 2) positioning has a significant effect on brand image with the value of t count is 8.957 t table is 1.9847 with a significance level of 0.000 less than 0.05. 3) Brand image has a significant effect on purchasing decisions with a tcount of 6.294 t table, namely 1.9847 with a significance level of 0.000 less than 0.05. 4) Positioning has a direct effect on purchasing decisions without going through brand image as a mediating variable with an effect value of 0.485.